Prospects for Using Two Alien Solidago L. Species, Invaded the Natural Communities of the Hron River (Slovakia) - Vinogradova, Yulia; Shelepova, Olga (Agrobiodiversity for Improving Nutrition, Health and Life Quality, 2020)
Resettlement of alien species Solidago canadensis L. and Solidago gigantea Ait. in the valley of the river Hron (Slovakia) has been studied. Since in some European countries these alien species began to be used as medicinal raw materials, the authors estimated their resource potential. The content of essential oil in leaves and inflorescences of both species was determined. It is noted that in the valley of the Hron River from the middle to the mouth, the number of local populations of Solidago canadensis gradual decrease. At the same time the number of local populations of Solidago gigantea gradual increase, and alone Danube this species grows in mass. In points of joint sprouting, the species differ in relation to the degree of humidification of habitats. A few plants with uncharacteristic edge of the leaf blades are noted. Analysis of the content of essential oil in the generative and vegetative organs of plants showed that the leaves (there is only a vegetative part) of Solidago gigantea contains a minimum amount of essential oil – 0.1%. Several large levels of essential oil are found in inflorescences (vegetative and generative organs are present) of plants – 0.3%. A significantly higher content of essential oil is fixed in the leaves of Solidago canadensis (up to 0.7%), and the maximum amount of essential oil is produced in the inflorescences – up to 0.9%. Thus, leaves and inflorescences of Solidago gigantea contain less essential oil than Solidago canadensis. Maximum levels of essential oil was produced by Solidago canadensis, growing on fertile, well-moistened floodplain soils.